Обґрунтування оптимальних параметрів армованих цегляних стовпів при будівництві багатоповерхового житлового будинку - Мельник, Сергій Олександрович; Melnyk, Serhiy (ЦНТУ, 2024)
На основі проведених експериментально- теоретичних досліджень оцінено вплив методу посилення центрально- та позацентрово стиснутих цегляних стовпів та залізобетонних колон з використанням вугле- та скловолокон на їх несучу здатність та розроблено методику розрахунку зазначених конструкцій. За результатами експериментальних досліджень надано пропозиції щодо методики розрахунку несучих цегляних стовпів (простінків) та залізобетонних колон, посилених зовнішнім армуванням з композиційних матеріалів на основі вугле- та скловолокон, та виконано оцінку існуючих розрахункових підходів до оцінки міцності залізобетонних колон, посилених композиційними матеріалами. Based on the conducted experimental and theoretical studies, the influence of the method of strengthening centrally and eccentrically compressed brick columns and reinforced concrete columns using carbon and glass fibers on their bearing capacity was assessed, and a calculation method for these structures was developed. Based on the results of experimental studies, proposals were made regarding the calculation method for load-bearing brick columns (sheets) and reinforced concrete columns reinforced with external reinforcement made of composite materials based on carbon and glass fibers, and an assessment of existing calculation approaches to assessing the strength of reinforced concrete columns reinforced with composite materials was performed.
Substantiation of optimal parameters of reinforced brick pillars in the construction of a multi-storey residential building
Keywords: цегла; стовп; кладка; brick; pillar; masonry